Design and test of robotic harvesting system for cherry tomato - Feng, Qingchun; Zou, Wei; Fan, Pengfei; Zhang, Chunfeng; Wang, Xiu (International Journal of Agricultural and Biological Engineering, 2018)
Harvesting of fresh-eating cherry tomato was highly costly on labor and time. In order to achieve mechanical harvesting for the fresh-eating tomato, a new harvesting robot was designed, which consisted of a stereo visual unit, an end-effector, manipulator, a fruit collector, and a railed vehicle. The robot configuration and workflow design focused on the special cultivating condition. Three key parts were introduced in detail: a railroad vehicle capably moving on both ground and rail was adopted as the robot’s carrier, a visual servo unit was used to identify and locate the mature fruits bunch, and the end-effector to hold and separate the fruit bunch was designed based on the stalk’s mechanical features. The field test of the new developed robot was conducted and the results were analyzed. The successful harvest rate of the robot was 83%, however, each successful harvest averagely needed 1.4 times attempt, and a single successful harvesting cycle cost 8 s excluding the time cost on moving.Keywords: cherry tomato, harvesting robot, visual servo, configuration design, field testDOI: 10.25165/j.ijabe.20181101.2853Citation: Feng Q C, Zou W, Fan P F, Zhang C F, Wang X. Design and test of robotic harvesting system for cherry tomato. Int J Agric & Biol Eng, 2018; 11(1): 96–100.